Raymond Williams’s Sociology of Culture - Jones, P. author. aut Link
XX, 247 p.
Keywords: This detailed study of Williams unlocks his late sociology of culture. It covers previously overlooked aspects, such as his critique of Birmingham cultural studies, his use of an Adorno-like approach to 'cultural production', his 'social formalist' alternative to structuralism and post-structuralism and his approach to 'the media'.